2014
DOI: 10.1136/neurintsurg-2013-010990.rep
|View full text |Cite
|
Sign up to set email alerts
|

Endovascular repair of direct carotid–cavernous fistula in Ehlers–Danlos type IV

Abstract: Ehlers-Danlos syndrome (EDS) type IV is a collagen vascular disease with an autosomal dominant inheritance caused by COL3A1 mutation. Patients with EDS type IV can present with organ rupture, spontaneous arterial dissections and ruptured aneurysms. Because of their propensity to form arterial dissections, aneurysms and rupture, they can develop carotidcavernous fistula (CCF) after minor trauma or spontaneously. In EDS, it has been reported that even conventional catheter diagnostic angiography may result in la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…Sex was not reported for 7 (7.2%) individuals [ 21 , 40 ]. Median age at direct CCF diagnosis was 31.0 years, IQR [24.0–39.0] (one missing value [ 34 ]). Pepin et al reported an overall mean age of 30.9 years in 27 patients.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Sex was not reported for 7 (7.2%) individuals [ 21 , 40 ]. Median age at direct CCF diagnosis was 31.0 years, IQR [24.0–39.0] (one missing value [ 34 ]). Pepin et al reported an overall mean age of 30.9 years in 27 patients.…”
Section: Resultsmentioning
confidence: 99%
“…There were 5 Glycine missense variants [ 5 , 8 , 18 , 51 , 53 ] and 4 splice-site variants [ 8 , 29 , 45 , 51 ]. In the other patients, vEDS diagnosis was made either on relevant clinical examination, imaging and medical history [ 6 , 7 , 9 , 10 , 12 , 15 , 19 , 27 , 28 , 30 , 31 , 33 , 34 , 39 , 42 , 46 50 , 52 ], histological findings [ 6 , 9 , 24 , 27 , 32 , 43 , 44 , 47 ] or on fibroblast culture [ 8 , 15 , 36 , 38 , 40 , 43 , 44 ]. Imaging described marked tortuosity or dysplastic aspect or ectasia of the ICA segment in the neck [ 6 , 10 , 19 , 26 , 39 , 49 ], sometimes associated with an aneurysm rupture of the intracranial ICA segment into the CS [ 8 , 15 , 19 ].…”
Section: Resultsmentioning
confidence: 99%
“…A recent report showed more encouraging results, probably due to medical progress over time. Linfante et al presented a case of successful management of a carotid cavernous fistula in a patient with confirmed vEDS [ 19 ]. In another case of a ruptured subclavian artery aneurysm in a confirmed case of vEDS, Lida et al described how they managed the case successfully with transcatheter coil embolization [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Angiogram demonstrated that dissection extended to the distal ICA occlusion; therefore, dissection involving the intracranial ICA may have resulted in acute occlusion and present a CCF, simultaneously. A study reported a CCF related to dissection of the ICA, 6) but there has been no case report on ICA-dissection-related occlusion complicated by a CCF. In the present case, concerning the CCF before aspiration, cavernous sinus was slightly visualized in the arterial phase, its shunt flow was small, and the CCF was asymptomatic.…”
Section: Discussionmentioning
confidence: 99%